ANALISIS PROSES EVALUASI PEMBELAJARAN PADA MATA KULIAH EVALUASI PENDIDIKAN SENI TARI - Ranti Arfira Nofeni; Astuti, Fuji; Yuliasma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the learning evaluation process in the Dance Arts Education Evaluation course. Learning evaluation is an essential component of the educational process as it functions to measure the achievement of learning objectives, particularly in dance education, which emphasizes cognitive, affective, and psychomotor aspects. This research employed a qualitative approach using a descriptive method. The research subjects consisted of the course lecturer and students participating in the Dance Arts Education Evaluation course. Data were collected through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the learning evaluation process in the Dance Arts Education Evaluation course has included evaluation planning, evaluation implementation, and follow-up of evaluation results. The forms of evaluation used include assignment assessment, practical assessment, and final examinations, which are adjusted to the characteristics of dance learning. However, several constraints were still found, such as limited time and a lack of variety in assessment instruments. Therefore, it is necessary to develop more varied and contextual evaluation strategies so that the dance learning process can be carried out optimally.